2010
DOI: 10.1029/2009wr008006
|View full text |Cite
|
Sign up to set email alerts
|

Age dating base flow at springs and gaining streams using helium‐3 and tritium: Fischa‐Dagnitz system, southern Vienna Basin, Austria

Abstract: [1] Springs and gaining streams are locations where groundwater flow paths naturally converge and discharge as a flow-weighted mixture of water from the contributing aquifer. The age of that water is therefore a good measure of the mean transit time (MTT) of the contributing aquifer. The question examined in this paper is whether tritiogenic helium-3 and tritium ( 3 He trit -3 H) can be used to estimate MTT in these settings. To answer that question two factors must be considered: (1) the loss of 3 He from dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 20 publications
(21 reference statements)
1
57
0
Order By: Relevance
“…Stolp et al (2010) noted that tracer concentrations measured in-river are related to inflow rate and subsequent losses, and Gardner et al (2011a) further defined the following ratio when sampling for helium in rivers:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stolp et al (2010) noted that tracer concentrations measured in-river are related to inflow rate and subsequent losses, and Gardner et al (2011a) further defined the following ratio when sampling for helium in rivers:…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, discharge from springs may originate within a catchment (e.g., Ellins et al, 1990), or from an external basin (e.g., Solomon et al, 2010). Thus, variable water sources for baseflow can be expected, and methods for characterization have been challenged not only to define rates and locations, but also to begin defining flow-weighted mixtures of groundwater spanning different time scales (e.g., Stolp et al, 2010;Solomon et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Systems presented in section 3 -and more generally, any system whose flow paths are analytically described -can be plugged together to generate composite RTDs. Examples of linear combinations include the exponential and dispersion models (Stolp et al, 2010), exponential and shape-free models (Goderniaux et al, 2013), two piston flow models (Eberts et al, 2012), exponential and piston-flow models (Eberts et al, 2012;Solomon et al, 2010), two exponential-piston-flow models (Green et al, 2014), and multiple dispersion models (Engdahl and Maxwell, 2014;Long and Putnam, 2009;McCallum et al, 2014).…”
Section: Steady-state Analytical Rtdsmentioning
confidence: 99%
“…Zuber et al, 2005;Stewart and Thomas, 2008;Einsiedl et al, 2009;Manning et al, 2012;Blavoux et al, 2013) and for the assessment of TT in surface water studies (Matsutani et al, 1993;Stewart et al, 2007;Morgenstern et al, 2010;Stolp et al, 2010;Stewart, 2012;Gusyev et al, 2013;Kralik et al, 2014). Most of these studies had to assume stationarity of the observed system by deriving a unique estimate of TT or RT from 3 H time-series data, in order to circumvent the bomb pulse issue.…”
Section: Introductionmentioning
confidence: 99%